2022
DOI: 10.21203/rs.3.rs-2174016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durvalumab plus tremelimumab for the treatment of advanced neuroendocrine neoplasms of gastroenteropancreatic and lung origin: the phase II DUNE trial (GETNE 1601)

Abstract: Single immune checkpoint blockade in advanced neuroendocrine neoplasms (NENs) shows limited efficacy; dual checkpoint blockade may improve treatment activity. Dune is a non-randomized controlled multicohort phase II clinical trial evaluating durvalumab plus tremelimumab activity and safety in advanced NENs. This study included 123 patients presenting between 2017 and 2019 with typical/atypical lung carcinoids (Cohort (C) 1), G1/2 gastrointestinal (C2), G1/2 pancreatic (C3) and G3 gastroenteropancreatic (GEP) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The median OSs were 29.5 mo, 23.8 mo, and 5.9 mo, respectively[ 40 ]. The 9-month DCRs for these cases were 22.8% (95%CI: 16.0-30.8), and 35.5% (95%CI: 20.5-53.0), 25% (95%CI: 12.6-41.7), and 6.1% (95%CI: 1.3-18.1) for C2 to C4, respectively[ 41 ]. Therefore, this study showed that the therapeutic effectiveness of dual ICI therapy in well-differentiated NENs was limited after the failure of standard treatment and had a relatively lower ORR.…”
Section: Combined Immunotherapy For Nens Of the Digestive Systemmentioning
confidence: 99%
“…The median OSs were 29.5 mo, 23.8 mo, and 5.9 mo, respectively[ 40 ]. The 9-month DCRs for these cases were 22.8% (95%CI: 16.0-30.8), and 35.5% (95%CI: 20.5-53.0), 25% (95%CI: 12.6-41.7), and 6.1% (95%CI: 1.3-18.1) for C2 to C4, respectively[ 41 ]. Therefore, this study showed that the therapeutic effectiveness of dual ICI therapy in well-differentiated NENs was limited after the failure of standard treatment and had a relatively lower ORR.…”
Section: Combined Immunotherapy For Nens Of the Digestive Systemmentioning
confidence: 99%